Curriculum Alignment and Skill Acquisition: A Case Study of CEFR Implementation on Speaking Course - Hadianti, Siti; Hidayah; Benny Nugraha; Suci Madiarti Isman; Roihatul Millah; Anugrah Murtini (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Students' English proficiency is often measured by their skills in listening, speaking, reading, and writing. Among these, speaking is a primary focus of the English Education Department at Universitas Terbuka (UT). To assess whether students reach the desired level of proficiency, the department relies on standardized frameworks like the Common European Framework of Reference (CEFR). UT's curriculum on the Speaking course highlights the importance of CEFR, specifying that teaching should foster skills progression in English from elementary (A2) to intermediate (B2) levels. Despite this, there is a need to evaluate whether the implementation aligns with the curriculum's objectives, as the real-world application sometimes falls short of these standards. This research adopts a case study approach using mixed methods, combining qualitative and quantitative data in three regions. The result shows that the curriculum of speaking classes is based on the CEFR at the B2 level.